PEMBUATAN PEMBANGKIT LISTRIK TENAGA MIKROHIDRO TURBIN ULIR SKALA LABORATORIUM - Esron Robet Lubis (LPPM Politeknik LP3I Medan, 2022)
River flow is one of the renewable energy sources that can be used for micro hydro power plant